2022
DOI: 10.3389/fnut.2022.894557
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Eating Identities With Self-Reported Dietary Behaviors and Body Mass Index

Abstract: Objective:To inform dietary interventions, it is important to understand antecedents of recommended (henceforth: healthy) dietary behaviors, beyond dietary beliefs and self-efficacy. We used the validated “Eating Identity Type Inventory” to assess the extent to which participants identified as healthy eaters, meat eaters, emotional eaters or picky eaters. We examined correlations between participants' race/ethnicity and other socio-demographic characteristics and affinity with these eating identities, how affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…There was a significant association between self-perception of a healthy diet and higher binary and graded EWG scores, with the association strongest in the high SES group as well as in those participants who were not in employment at the time of dietary data collection. This replicates previous research that has shown associations between self-perceived diet and more objective measures of dietary quality [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…There was a significant association between self-perception of a healthy diet and higher binary and graded EWG scores, with the association strongest in the high SES group as well as in those participants who were not in employment at the time of dietary data collection. This replicates previous research that has shown associations between self-perceived diet and more objective measures of dietary quality [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…There has also been an increased interest in recent years as to the impact and importance of whether individuals believe they eat a healthy diet. Individuals who believe they are healthier eaters have been shown to have healthier dietary behaviours (27), to eat more fruits and vegetables and to eat fewer discretionary foods (28). It is unclear whether those who feel they eat a healthier diet have a greater adherence to the EWG in the context of a UK and Irish population however, this knowledge could be valuable for helping to identify those who may benefit from dietary advice or intervention and warrants investigation.…”
Section: Introductionmentioning
confidence: 99%